Elementary School Principals and Leadership Development - Joanne S. Burgess; R. Allan Dermott (Journal of Research in Rural Education, 1983)
This study investigated the value of selected leadership competencies of elementary principals as perceived by superintendents, supervising principals, teaching principals, teachers under supervising principals, and teachers under teaching principals. A questionnaire of 54 items covered three areas of administrative skill: technical, conceptual, and human. Differences were found between groups on 29 of the 54 items, with the major differences appearing in the human skill area. The findings include: (I) teaching principals are in closer agreement with their teachers than are supervising principals; (2) the values of educators change as individuals move from active classroom work to active involvement with adminstrative tasks.